Iridium monatomic loaded cobalt oxide-graphene aerogel self-supporting material as well as preparation method and application thereof
By anchoring iridium single atoms on the cobalt oxide-graphene aerogel self-supporting material, the problem of insufficient performance of existing electrocatalytic oxygen reduction reaction catalysts is solved, and efficient and stable oxygen reduction catalytic effect is achieved, which is suitable for the development of electrolytic water technology.
Patent Information
- Application Number
- CN202411779185.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-05
AI Technical Summary
In the existing electrolytic water technology, the performance of electrocatalytic oxygen reduction reaction (ORR) catalysts is insufficient, especially the development of general-purpose catalysts under acidic, alkaline and neutral conditions is difficult, and the precious metal reserves of traditional iridium-based catalysts are scarce, and single-atom catalysts are unstable.
By anchoring iridium in the form of a single atom on the cobalt oxide-graphene aerogel self-supporting material, cobalt oxide with metal defects was prepared as a support by using solvothermal method and freeze-drying technology. The Ir single atoms were dispersed at the metal defect site, and the graphene aerogel formed a three-dimensional porous network to improve the activity and stability of the catalyst.
It has achieved efficient promotion of oxygen reduction reaction at lower voltages, higher catalytic activity and improved stability, and is suitable for the preparation of oxygen reduction catalysts for electrolyzed water, reducing the consumption of precious metals.
Smart Images

Figure CN119710813A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrolytic water catalytic materials, and in particular relates to a cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms, and a preparation method and application thereof. Background Art
[0002] Hydrogen energy is one of the most ideal clean energy sources and has attracted widespread attention. Electrolysis of water has become a promising clean energy conversion technology because of its abundant raw materials and its ability to be used in conjunction with power generation systems such as solar energy, wind energy, and tidal energy. Among them, the electrocatalytic oxygen reduction reaction (ORR) is one of the core technologies of electrolysis of water, which restricts the large-scale commercial development of electrolysis of water. The ORR reaction is largely affected by the performance of the catalyst, especially the development of universal catalysts suitable for acidic, alkaline, and neutral conditions is very urgent. Traditional iridium-based catalysts catalyze in the form of alloys, iridium oxides, etc. However, the reserves of these precious metals in nature are very small. Single-atom catalysts refer to catalysts composed of single atoms, which can promote atomic dispersion and rich surface transition states, and have high catalytic performance and selectivity compared to traditional catalysts. Therefore, it is urgent to develop single-atom catalysts to reduce the consumption of iridium and further promote the development of electrolysis of water.
[0003] Iridium is anchored on the surface of the catalyst carrier in the form of a single atom, so that the utilization rate of expensive iridium is maximized. At the same time, there is a strong interaction between the oxide carrier and the iridium single atom, which makes it show unique catalytic performance. Metal oxides (TiO2, ZnO, Co3O4, Mn3O4) are the most common electrochemically stable catalyst carriers, with the characteristics of low raw materials, no environmental pollution, and high safety. However, this type of carrier still has problems such as poor conductivity and low volume activity, which limits its commercialization process. Moreover, most of the single-atom catalysts currently on the market are iridium atoms adsorbed on the surface or anchored in oxygen defects. The interaction between the active atoms and the metal oxide carrier in the system is relatively weak, and the active sites are relatively unstable and easy to ripen and agglomerate, so that the activity and stability of the catalyst show poor results.
[0004] At present, graphene aerogel (3DNG) as a new type of catalyst carrier has shown potential in oxygen reduction catalysts of non-precious metal oxide nanoparticles. Graphene aerogel has high conductivity, large specific surface area, chemical stability and good adhesion, which has obvious advantages over traditional carriers. In addition, the three-dimensional porous network structure of graphene aerogel is conducive to increasing the active surface area and mass transfer efficiency of the catalyst, thereby improving the performance of the catalyst.
[0005] However, the synthesis of graphene aerogel composite catalysts still faces challenges, such as the control of pore number, size, hardness, and the stacking of metal oxides and carriers. In addition, synergistic effects play an important role in performance improvement, but their construction methods and mechanisms need further study. Therefore, how to effectively use graphene aerogel as a catalyst carrier and achieve successful application is still a key issue that needs to be explored. Summary of the invention
[0006] In order to solve the problems of the above-mentioned prior art, the first purpose of the present invention is to provide a method for preparing a cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms, which has mild process conditions and simple operation, and can prepare a new self-supporting catalyst material composed of graphene aerogel (3DNG) and Ir-Co3O4, which synergistically improves the electrocatalytic activity and catalytic stability of the catalyst, and is suitable for the preparation and application of electrocatalytic oxygen reduction catalysts.
[0007] The second object of the present invention is to provide a cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms prepared by the above preparation method.
[0008] The third object of the present invention is to provide an application of the above-mentioned cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms.
[0009] One of the purposes of the present invention is to adopt the technical solution:
[0010] A method for preparing a cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms comprises the following steps:
[0011] Step (1): mixing a soluble cobalt salt in glycerol to obtain a mixed slurry; subjecting the mixed slurry to a solvothermal reaction at a temperature of 170 to 190° C. to obtain a cobalt oxide precursor;
[0012] Step (2): mixing chloroiridic acid, the cobalt oxide precursor, and a polyvinyl alcohol aqueous solution, and further adding graphene to mix, to obtain a hydrogel; replacing unreacted ions in the hydrogel, and then freeze-drying to obtain an aerogel precursor; wherein the mass ratio of chloroiridic acid, cobalt oxide precursor, and graphene is (18-25): (40-60): (5-10);
[0013] Step (3): calcining the aerogel precursor to obtain a cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms.
[0014] As an improved solution, in step (1), the soluble cobalt salt is one or more of cobalt acetate, cobalt oxalate, and cobalt chloride. Further preferably, the soluble cobalt salt is cobalt acetate. As a further improved solution, the amount of the soluble cobalt salt used is 0.5 to 2.0 g per 30 mL of glycerol.
[0015] As an improved solution, in step (1), the solvent thermal reaction time is 1 to 3 hours. The solvent thermal reaction is a reaction carried out in a closed high-temperature and high-pressure reactor as generally understood in the art. In the present invention, a solvable cobalt salt is subjected to a solvent thermal reaction in a reactor in the presence of glycerol, thereby preparing a cobalt oxide precursor that is uniformly dispersed and conducive to the construction of metal defect sites.
[0016] As an improved solution, in step (2), the mass concentration of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 15-20 mg / mL; and the relative molecular mass of the polyvinyl alcohol is 50,000-100,000.
[0017] As an improved solution, the usage ratio of chloroiridic acid, cobalt oxide precursor, and polyvinyl alcohol aqueous solution is (18-25) mg: (40-60) mg: (600-800) μL.
[0018] As a further improved solution, in step (2), when preparing the hydrogel, the graphene added is specifically a graphene aqueous solution, which is prepared by the Hummers method; the concentration of graphene in the graphene aqueous solution is 1.8 to 2.2 mg / mL.
[0019] As an improved solution, in step (2), the replacement is performed by adding a water-methanol mixture; the volume percentage of methanol in the water-methanol mixture is 5% to 20%, and more preferably 10%; and the freeze-drying time is 15 to 30 hours.
[0020] As an improved solution, in step (3), the calcination is carried out in a hydrogen / argon mixed gas; the calcination temperature is 500-700° C., and the calcination time is 8-15 hours.
[0021] The second object of the present invention is to adopt the following technical solution:
[0022] The cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms prepared by the above preparation method.
[0023] The present invention adopts the above-mentioned preparation method to prepare the obtained material, using cobalt oxide with metal defects as the metal carrier, and Ir is dispersed in the metal defect site in the form of single atoms; at the same time, the graphene aerogel forms a strong three-dimensional porous network, avoiding the restacking of graphene, providing a large number of active centers for ORR reaction, and maximizing the catalytic performance.
[0024] As a further improved technical solution, in the cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms, the loading amount of iridium single atoms is 1 wt% to 4 wt%.
[0025] The third object of the present invention is to adopt the following technical solution:
[0026] The above-mentioned cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms is used as a catalyst in the oxygen reduction reaction of the catalytic water electrolysis process.
[0027] Compared with the prior art, the beneficial effects of the present invention are mainly:
[0028] The preparation method of the cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms provided by the present invention, firstly utilizes soluble cobalt salt and glycerol to carry out solvothermal reaction, forms metal compound with polyglycerol coordination by solvothermal method, thereby creates oxygen-rich environment, then adds iridium metal ion to immerse in the interlayer of metal organic compound, then adds graphene to form aerogel precursor, and finally carries out calcination, thereby in the process of forming metal defects in situ, anchors nanometer single atom iridium in defect vacancy of metal oxide carrier, forms single atom iridium electrocatalyst material of lattice confinement. The above-mentioned synthesis strategy adopted by the present invention, utilizes the method combining solvothermal self-assembly with freeze drying, successfully prepares the self-supporting catalyst material of oxygen reduction of 3DNG and Ir-Co3O4 composite. The catalytic material has a higher starting potential in alkaline medium than the composite catalyst (Co3O4 / NG) of three-dimensional nitrogen-doped graphene aerogel and nitrogen-doped graphene and cobalt tetraoxide, which means that the catalyst can effectively promote oxygen reduction reaction at a lower voltage, and the catalytic activity is higher.
[0029] The above method of the present invention prepares a carrier precursor by a solvothermal method, then uses an impregnation method to load Ir atoms, and finally adds graphene to form a hydrogel and calcines it, thereby obtaining a sandwich-shaped cobalt oxide-graphene aerogel self-supporting electrode material. The catalyst material uses an oxide with metal defect sites as a carrier, and Ir is dispersed in the metal defect sites in the form of single atoms. In addition, the present invention can achieve single-atom-level dispersion of Ir by strictly controlling each reaction condition. At the same time, the metal defects in the present invention anchor the Ir single atoms well, further improving the catalytic stability of the material; the catalyst has a higher starting potential, charge transfer number and limiting current density than three-dimensional nitrogen-doped graphene aerogel in an alkaline medium, a lower hydrogen peroxide yield, and better durability than commercial Pt / C catalysts.
[0030] In addition, the metal defect oxide precursor used in the present invention is highly designable, easy to anchor dispersed single atoms, and is conducive to the large-scale preparation of metal oxide-loaded iridium single-atom electrocatalysts; and the impregnation solution involved can be collected by centrifugation and continued to be used, which helps to reduce the cost of large-scale production.
[0031] Finally, the present invention successfully prepared a sandwich-shaped cobalt oxide-graphene aerogel self-supporting electrode material by using a strategy of glycerol capping to create metal defects and then anchoring single atoms. The above-mentioned single-atom synthesis method successfully developed by the present invention effectively overcomes the current situation of instability of single-atom catalysts in the prior art and has high industrial utilization value. At the same time, the material provided by the present invention has a higher half-wave potential, electron transfer number and lower H2O2 yield in an alkaline medium.
[0032] In the catalytic material of the present invention, the higher oxygen reduction performance is due to the good structure: 1) 3DNG, as an electron donor, continuously transports electrons to Co3O4, providing the necessary conditions for oxygen reduction; 2) The strong three-dimensional porous network avoids the restacking of graphene, provides a large number of active centers for ORR reaction, maximizes the catalytic activity of the catalyst, and allows a high diffusion rate of the electrolyte; 3) 3DNG can not only maximize the active sites of the catalyst, but also effectively inhibit the aggregation and desorption of catalyst particles, thereby synergistically improving the electrocatalytic activity and catalytic stability of the catalyst, and has a strong prospect for industrial application in the field of oxygen reduction catalyst preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings used in the embodiments and test examples; it should be understood that the following drawings only illustrate some test examples of the present invention and should not be regarded as limiting the scope of protection of the rights;
[0034] Figure 1 The XRD diagram of the cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms in Examples 1 to 5 of the present invention;
[0035] Figure 2 This is an electron image of the cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms in Example 1 of the present invention;
[0036] Figure 3 This is a SEM image of the cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms in Example 1 of the present invention;
[0037] Figure 4 This is a spherical aberration diagram of the cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms in Example 1 of the present invention;
[0038] Figure 5 This is a LSV performance diagram of the cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms in Example 1 of the present invention;
[0039] Figure 6 This is a CV performance diagram of the cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms in Example 1 of the present invention;
[0040] Figure 7 This is a function diagram of the peroxide percentage and the number of electron transfers of the cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms in Example 1 of the present invention relative to the potential. DETAILED DESCRIPTION
[0041] In order to make the technical purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and Examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the scope of protection of the present invention. In the following examples, the raw materials or reagents involved are conventional materials or reagents that can be obtained through commercial channels unless otherwise specified.
[0042] The present invention provides a method for preparing a cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms, comprising the following steps:
[0043] Step (1): mixing a soluble cobalt salt in glycerol to obtain a mixed slurry; subjecting the mixed slurry to a solvothermal reaction at a temperature of 170 to 190° C. to obtain a cobalt oxide precursor;
[0044] Step (2): mixing chloroiridic acid, the cobalt oxide precursor, and a polyvinyl alcohol aqueous solution, and further adding graphene to mix, to obtain a hydrogel; replacing unreacted ions in the hydrogel, and then freeze-drying to obtain an aerogel precursor; wherein the mass ratio of chloroiridic acid, cobalt oxide precursor, and graphene is (18-25): (40-60): (5-10);
[0045] Step (3): calcining the aerogel precursor to obtain a cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms.
[0046] In the present invention, in step (1), there is no particular limitation on the soluble cobalt salt, and any cobalt salt that can be dissolved in glycerol and is well known to those skilled in the art can be used. Specifically, the soluble cobalt salt is one or more of cobalt acetate, cobalt oxalate, and cobalt chloride; more preferably, the soluble cobalt salt is cobalt acetate.
[0047] In the present invention, the amount of the soluble cobalt salt used is 0.5 to 2.0 g, more preferably 1 g, per 30 mL of glycerol.
[0048] The present invention allows a solvable cobalt salt to undergo a solvothermal reaction in a reactor in the presence of glycerol. The solvothermal reaction is a reaction carried out in a sealed high-temperature and high-pressure reactor. The present invention uses a solvothermal reaction to prepare a cobalt oxide precursor that is uniformly dispersed and conducive to the construction of metal defect sites. Preferably, in step (1), the solvothermal reaction time is 1 to 3 hours.
[0049] Preferably, in step (1), after the solvent thermal reaction, the step of washing and drying the product obtained by the reaction is also included. The present invention does not specifically limit the washing method, and those skilled in the art can adopt a well-known washing method, which only needs to meet the washing requirements of the reactants. For example, the washing is specifically carried out by alcohol washing, and the solvent used for alcohol washing can be one or more of ethanol, methanol, and isopropanol. In the following embodiments, alcohol washing is used for washing, and the solvent used for alcohol washing is specifically isopropanol. Further, the present invention does not specifically limit the drying method, and those skilled in the art can adopt well-known drying conditions, which only needs to meet the drying requirements of the reactants. For example, the drying temperature is 60 to 90°C, and the drying time is 10 to 48h. In the following embodiments, the drying temperature is specifically 75°C, and the drying time is specifically 24h.
[0050] In the present invention, in step (2), the mass concentration of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 15-20 mg / mL; more preferably, the relative molecular mass of polyvinyl alcohol is 50,000-100,000.
[0051] In the present invention, in step (2), the usage ratio of chloroiridic acid, cobalt oxide precursor and polyvinyl alcohol aqueous solution is (18-25) mg: (40-60) mg: (600-800) μL.
[0052] The present invention does not specifically limit the use form of graphene involved in the preparation method, and any graphene source familiar to technicians can be used. In the following embodiments, graphene is specifically added as a graphene aqueous solution; the graphene aqueous solution is prepared by the Hummers method, and the concentration of graphene in the graphene aqueous solution is 1.8 to 2.2 mg / mL. In other embodiments, graphene can also be commercially available solid graphene, and then the graphene is formulated into an aqueous solution for use.
[0053] In the present invention, in step (2), graphene is added and mixed evenly, and the mixture is mixed evenly by vigorous shaking to form a hydrogel.
[0054] In the present invention, in step (2), the replacement is performed by adding a water-methanol mixture; the volume percentage of methanol in the water-methanol mixture is 5% to 20%, more preferably 10%; and the freeze-drying time is 15 to 30 hours. The present invention does not impose any particular limitation on the number of replacements, which only needs to ensure the replacement effect. Preferably, the number of replacements is 2 to 5 times.
[0055] In the present invention, in step (3), calcination is carried out in a hydrogen / argon mixed gas; the calcination temperature is 500-700°C, and the calcination time is 8-15h. The present invention adopts a calcination temperature of 500-700°C, which can effectively ensure that the obtained material is a single-atom catalyst material. If a temperature lower than 500°C is adopted, such as calcination at 400°C, after phase testing, the precursor cannot be decomposed, so a single-atom catalyst cannot be obtained. If a temperature higher than 700°C is adopted, such as calcination at 800°C, after phase testing, single atoms will overflow and agglomerate to form metal particles, and a uniformly dispersed single-atom catalyst cannot be obtained.
[0056] In step (3), the present invention does not impose any particular limitation on the calcination atmosphere. In preliminary experiments, the present invention has verified that calcination in air atmosphere, oxygen atmosphere, argon atmosphere, and nitrogen atmosphere does not affect the physical phase of the single-atom catalyst, and therefore does not affect the preparation effect of the material of the present invention. Preferably, in an embodiment of the present invention, calcination is carried out in a hydrogen / argon mixed gas, and the volume percentage of hydrogen in the mixed gas is 10%.
[0057] Example 1
[0058] This embodiment provides a cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms, and the preparation method thereof comprises the following steps:
[0059] (1) adding 1 g of cobalt acetate to 30 mL of glycerol, and stirring the mixture under magnetic stirring for 5 h to obtain a mixed slurry; transferring the obtained mixed slurry to a reactor with a polytetrafluoroethylene liner, and keeping the reactor at 180° C. for 2 h, and then cooling it naturally to room temperature; centrifuging the obtained reactant, washing with alcohol, drying and collecting the obtained reactant to obtain a cobalt oxide precursor;
[0060] (2) 0.02034 g of chloroiridic acid and 50 mg of the cobalt oxide precursor prepared in step (1) were dissolved in 625 μL of polyvinyl alcohol (PVA) aqueous solution (concentration 16 mg / mL) to obtain a mixed solution; the mixed solution was then mixed with 3 mL of graphene aqueous solution (2 mg / mL) prepared by the Hummers method, and the mixture was shaken vigorously to form a hydrogel; then a water-methanol mixture (methanol volume ratio of 10%) was added to the hydrogel and soaked for 24 hours to replace the unreacted ions in the hydrogel, and the replacement solution was replaced 3 times during the period; then, the hydrogel was used as a precursor and freeze-dried (24 hours) to obtain an aerogel precursor;
[0061] (3) The aerogel precursor obtained in step (2) is placed in a mold and calcined at 600° C. for 12 h at a flow rate of 10% H 2 / Ar to obtain a cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms, which is recorded as Ir-Co 3 O 4 -3DNG-PVA aerogel.
[0062] Embodiments 2 to 5
[0063] Examples 2 to 5 respectively provide a self-supporting material, and the preparation method thereof is carried out with reference to Example 1, except that: the amount of chloroiridic acid in Example 2 is adjusted to 0.00406 g, the amount of chloroiridic acid in Example 3 is adjusted to 0.01220 g, the amount of chloroiridic acid in Example 4 is adjusted to 0.02848 g, and the amount of chloroiridic acid in Example 5 is adjusted to 0 g, and the other conditions are the same as in Example 1.
[0064] Example 6
[0065] This embodiment provides a cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms, and the preparation method thereof comprises the following steps:
[0066] (1) adding 1 g of cobalt acetate to 30 mL of glycerol, and stirring the mixture under magnetic stirring for 5 h to obtain a mixed slurry; transferring the obtained mixed slurry to a reactor with a polytetrafluoroethylene liner, and keeping the reactor at 180° C. for 2 h, and then cooling it naturally to room temperature; centrifuging the obtained reactant, washing with alcohol, drying and collecting the obtained reactant to obtain a cobalt oxide precursor;
[0067] (2) 0.02034 g of chloroiridic acid and 50 mg of the cobalt oxide precursor prepared in step (1) were dissolved in 720 μL of PVA solution (concentration 16 mg / mL) to obtain a mixed solution; the mixed solution was then mixed with 3 mL of graphene aqueous solution (2 mg / mL) prepared by the Hummers method, and the mixture was shaken vigorously to form a hydrogel; then a water-methanol mixture (methanol volume ratio of 10%) was added to the hydrogel and soaked for 24 hours to replace the unreacted ions in the hydrogel, and the replacement solution was replaced 3 times during the period; then, the hydrogel was used as a precursor and freeze-dried (24 hours) to obtain an aerogel precursor;
[0068] (3) The aerogel precursor obtained in step (2) is placed in a mold and calcined at 600° C. for 12 h at a flow rate of 10% H 2 / Ar to obtain a cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms, which is recorded as Ir-Co 3 O 4 -3DNG-PVA aerogel.
[0069] Example 7
[0070] This embodiment provides a cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms, and the preparation method thereof comprises the following steps:
[0071] (1) adding 1 g of cobalt acetate to 30 mL of glycerol, and stirring the mixture under magnetic stirring for 5 h to obtain a mixed slurry; transferring the obtained mixed slurry to a reactor with a polytetrafluoroethylene liner, and keeping the reactor at 180° C. for 2 h, and then cooling it naturally to room temperature; centrifuging the obtained reactant, washing with alcohol, drying and collecting the obtained reactant to obtain a cobalt oxide precursor;
[0072] (2) 0.02034 g of chloroiridic acid and 50 mg of the cobalt oxide precursor prepared in step (1) were dissolved in 625 μL of PVA solution (concentration 16 mg / mL) to obtain a mixed solution; the mixed solution was then mixed with 5 mL of graphene aqueous solution (2 mg / mL) prepared by the Hummers method, and the mixture was shaken vigorously to form a hydrogel; then a water-methanol mixture (methanol volume ratio of 10%) was added to the hydrogel and soaked for 24 hours to replace the unreacted ions in the hydrogel, and the replacement solution was replaced 3 times during the period; then, the hydrogel was used as a precursor and freeze-dried (24 hours) to obtain an aerogel precursor;
[0073] (3) The aerogel precursor obtained in step (2) is placed in a mold and calcined at 600° C. for 12 h at a flow rate of 10% H 2 / Ar to obtain a cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms, which is recorded as Ir-Co 3 O 4 -3DNG-PVA aerogel.
[0074] Example 8
[0075] This embodiment provides a cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms, and the preparation method thereof comprises the following steps:
[0076] (1) adding 1 g of cobalt acetate to 30 mL of glycerol, and stirring the mixture under magnetic stirring for 5 h to obtain a mixed slurry; transferring the obtained mixed slurry to a reactor with a polytetrafluoroethylene liner, and keeping the reactor at 180° C. for 2 h, and then cooling it naturally to room temperature; centrifuging the obtained reactant, washing with alcohol, drying and collecting the obtained reactant to obtain a cobalt oxide precursor;
[0077] (2) 0.02034 g of chloroiridic acid and 40 mg of the cobalt oxide precursor prepared in step (1) were dissolved in 625 μL of PVA solution (concentration 16 mg / mL) to obtain a mixed solution; the mixed solution was then mixed with 3 mL of graphene aqueous solution (2 mg / mL) prepared by the Hummers method, and the mixture was shaken vigorously to form a hydrogel; then a water-methanol mixture (methanol volume ratio of 10%) was added to the hydrogel and soaked for 24 hours to replace the unreacted ions in the hydrogel, and the replacement solution was replaced 3 times during the period; then, the hydrogel was used as a precursor and freeze-dried (18 hours) to obtain an aerogel precursor;
[0078] (3) The aerogel precursor obtained in step (2) is placed in a mold and calcined at 600° C. for 12 h at a flow rate of 10% H 2 / Ar to obtain a cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms, which is recorded as Ir-Co 3 O 4 -3DNG-PVA aerogel.
[0079] Test Example 1: Material Structure Analysis
[0080] The self-supporting materials prepared in Examples 1 to 5 of the present invention were subjected to X-ray diffraction (XRD) analysis, and the cobalt oxide-graphene aerogel loaded with iridium single atoms prepared in Example 1 was further subjected to electronic appearance structure, scanning electron microscopy (SEM) and spherical aberration electron microscopy analysis. The results are as follows: Figures 1 to 5 As shown. Among them, Figure 1 This is the XRD diagram of the self-supporting material prepared in Examples 1 to 5 of the present invention. Figure 2 This is the electronic appearance image of the cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms prepared in Example 1. Figure 3 This is a SEM image of the cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms prepared in Example 1. Figure 4 This is a spherical aberration image of the cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms prepared in Example 1.
[0081] from Figure 1It can be seen from the XRD diagram in that the materials prepared in Examples 1 to 5 of the present invention all have a crystalline structure of cobalt tetroxide, and no diffraction peaks of other impurity phases appear.
[0082] Depend on Figure 2 As can be seen from the electronic picture in, the self-supporting material obtained after calcination in the mold of Example 1 has a rich macroporous structure inside.
[0083] Depend on Figure 3 From the SEM image, we can see that the Co3O4 nanoparticles are evenly embedded in the graphene aerogel, and this structure has considerable advantages. Unlike surface-supported catalysts, the above structure can effectively increase the loading mass of metal oxides. The graphene sheets wrap the octahedral nanoparticles between the layers like armor, increasing the contact area between Co3O4 and graphene and preventing the agglomeration of metal oxides. Moreover, this strong three-dimensional porous network structure can also provide a large number of active centers that can participate in the reaction, thereby maximizing the activity of the ORR catalyst.
[0084] Depend on Figure 4 It can be seen from the spherical aberration diagram that atoms of different phases are regularly and evenly distributed, among which Ir atoms are distributed in a single atom, which can reduce the precious metal loading and improve the atomic utilization rate.
[0085] Test Example 2: Material Performance Test
[0086] This test example performs a performance test on the cobalt oxide-graphene aerogel self-supporting material (Ir-Co3O4-3DNG-PVA) loaded with iridium single atoms prepared in Example 1. Among them, the LSV performance test is a linear voltammetric scan at a scanning potential range of 0-1.2V and a scanning speed of 10mV / s, and the scanning is carried out under alkaline conditions. The CV performance test is a cyclic voltammetric scan at a scanning potential range of 0-1.2V and a scanning speed of 10mV / s. In order to further quantify the oxygen reduction electron transfer pathway of the aerogel, the present invention adopts a rotating ring disk electrode (RRDE) technology to measure the H2O2 yield generated on the ring disk electrode, and takes the ratio of the ring current to the total measured current, which is normalized by the calibrated collection efficiency (0.37) to estimate the fraction of peroxides produced. When testing the peroxide percentage and the number of electron transfers, the rotation speed is 1600rpm.
[0087] in, Figure 5 This is the LSV performance spectrum of the cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms in Example 1; Figure 6 The CV performance spectrum of the cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms in Example 1; Figure 7This is a graph showing the peroxide percentage and the number of electron transfers of the cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms in Example 1 as a function of the potential.
[0088] Figure 5 In the above, "3DNG" is a sample of nitrogen-doped graphene aerogel without iridium loading, which is a commercially available product; "Co3O4-3DNG-PVA" is prepared by referring to the preparation method of Example 1, but no iridium compound is added during the preparation, that is, the iridium chloride in step (2) of Example 1 is omitted during the preparation, and other conditions and process parameters remain unchanged. The prepared catalytic material is Co3O4-3DNG-PVA. Figure 6 In the above, "3DNG" has the same meaning as above, and the preparation method of "Co3O4-3DNG" is based on Example 1, except that the iridium chloride and PVA solution in step (2) are omitted, and only 50 mg of the cobalt oxide precursor prepared in step (1) is mixed with 3 mL of the graphene solution, and other conditions and process parameters remain unchanged to obtain the obtained material.
[0089] Depend on Figure 5 It can be seen from the LSV spectrum that the Ir-Co3O4-3DNG-PVA catalytic material prepared in Example 1 of the present invention has a higher starting potential than 3DNG and Co3O4-3DNG-PVA catalytic materials, and can effectively promote the oxygen reduction reaction at a lower voltage, and has a higher catalytic activity. In addition, the LSV curve of the catalytic material in Example 1 presents a typical S-shaped curve. The oxygen reduction reaction begins at 0.91V, and an oxygen reduction current is generated immediately. Then, as the potential shifts negatively, the oxygen reduction current increases significantly until a very obvious gentle slope appears. When the potential is lower than 0.70V, the oxygen reduction reaction enters the diffusion control region, and a current platform appears in the polarization curve, but there is still a weak current slope in the platform area.
[0090] Depend on Figure 6 It can be seen that the cyclic voltammetry curve of the catalyst material prepared in Example 1 of the present invention has a more obvious peak, indicating better redox performance. The peaks of the other two catalyst materials (3DNG and Co3O4-3DNG) are not obvious, especially 3DNG has no obvious redox peak.
[0091] Depend on Figure 7 The results show that during the test, the peroxide fraction of the cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms prepared in Example 1 in the range of 0.1-0.9V was less than 20%, and the electron transfer number was about 3.8, which proves that the catalyst has very good electron selectivity.
[0092] In summary, the method for preparing a cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms provided by the present invention uses a soluble cobalt salt and glycerol for a solvothermal reaction to form a metal organic compound with polyglycerol coordination to create an oxygen-rich environment, and then adds iridium metal ions thereto to immerse the metal organic compound in the interlayer, and then adds graphene to form an aerogel precursor and calcines it, thereby anchoring the nanometer single-atom iridium in the defect vacancy of the metal oxide carrier in the process of forming metal defects in situ, forming a lattice-confined single-atom iridium electrocatalyst material. The above method of the present invention can achieve the single-atom level dispersion of Ir, and the metal defects are good at anchoring the Ir single atoms, and the graphene aerogel forms a solid three-dimensional porous network, thereby synergistically improving the electrocatalytic activity and catalytic stability, which is suitable for the preparation and application of oxygen reduction catalysts.
Claims
1. A method for preparing a cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms, characterized in that: The following steps are involved: Step (1): mixing a soluble cobalt salt in glycerol to obtain a mixed slurry; subjecting the mixed slurry to a solvothermal reaction at a temperature of 170 to 190° C. to obtain a cobalt oxide precursor; Step (2): mixing chloroiridic acid, the cobalt oxide precursor, and a polyvinyl alcohol aqueous solution, and further adding graphene to mix, to obtain a hydrogel; replacing unreacted ions in the hydrogel, and then freeze-drying to obtain an aerogel precursor; wherein the mass ratio of chloroiridic acid, cobalt oxide precursor, and graphene is (18-25): (40-60): (5-10); Step (3): calcining the aerogel precursor to obtain a cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms.
2. The method for preparing the cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms according to claim 1, characterized in that: In step (1), the soluble cobalt salt is one or more of cobalt acetate, cobalt oxalate, and cobalt chloride; and the amount of the soluble cobalt salt used is 0.5 to 2.0 g per 30 mL of glycerol.
3. The method for preparing the cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms according to claim 1, characterized in that: In step (1), the solvent thermal reaction time is 1 to 3 hours.
4. The method for preparing the cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms according to claim 1, characterized in that: In step (2), the mass concentration of polyvinyl alcohol contained in the polyvinyl alcohol aqueous solution is 15-20 mg / mL; the relative molecular mass of the polyvinyl alcohol is 50,000-100,000.
5. The method for preparing the cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms according to any one of claims 1 to 4, characterized in that: The dosage ratio of chloroiridic acid, cobalt oxide precursor and polyvinyl alcohol aqueous solution is (18-25) mg: (40-60) mg: (600-800) μL.
6. The method for preparing the cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms according to any one of claims 1 to 4, characterized in that: In step (2), the replacement is performed by adding a water-methanol mixture; the volume percentage of methanol in the water-methanol mixture is 5% to 20%; and the freeze-drying time is 15 to 30 hours.
7. The method for preparing the cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms according to any one of claims 1 to 4, characterized in that: In step (3), the calcination is carried out in a hydrogen / argon mixed gas; the calcination temperature is 500-700° C., and the calcination time is 8-15 hours.
8. A self-supporting material of cobalt oxide-graphene aerogel loaded with iridium single atoms prepared by the preparation method according to any one of claims 1 to 7.
9. The cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms according to claim 8, characterized in that: In the cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms, the loading amount of the iridium single atoms is 1wt% to 4wt%.
10. An application of the cobalt oxide-graphene aerogel self-supporting material loaded with iridium single atoms as claimed in claim 8 or 9, characterized in that: Application as a catalyst in the oxygen reduction reaction in the catalytic water electrolysis process.
Citation Information
Patent Citations
Method for preparing graphene aerogel and graphene / metallic oxide aerogel
CN103413689A
Graphene-noble metal nanoparticle compound hydrogel and aerogel and preparing method and application thereof
CN106268631A
Universal preparation and application of nitrogen-rich graphene aerogel loaded monatomic cluster catalyst based on sol-gel method
CN111744522A
Preparation method of Co3O4-NiO-graphene aerogel catalyst material
CN113198477A
Electrode for producing hydrogen by electrolyzing water based on graphene aerogel and synthesis method thereof
CN114293218A